Svalbard Expedition - Siikavesi, Mikko (Haaga-Helia ammattikorkeakoulu, 2015)
This thesis is a written report on how to organise a trip for a small group of people. This thesis was commissioned by HAAGA-HELIA University of Applied Sciences and the author of this thesis is tourism student from the Bachelor Degree Programme in Tourism Mikko Siikavesi. The objective of this thesis was to organise a trip to Svalbard for a small group of people. The purpose was to arrange a successful trip for the customers. In the future this trip could be implemented by any tour operator. A theoretical framework was based on literature of Polar Tourism and Tourism in pe-ripheral areas as well as a guidebook of Svalbard. The activities that were implemented in this thesis can be sub-categorised as adventure tourism. Polar Tourism remains the main category because activities were executed in polar region. The aim of this thesis was to take a deeper look of how an independent tour operator can work in Svalbard. Which problems may occur and what rules and regulations may apply for non-resident tour operators. Also subjects such as how polar tourism is affecting the fragile environment are covered in this thesis.